The makerspace librarian's sourcebook - Kroski, Ellyssa (ALA Editions, an imprint of the American Library Association, 2017)
Library makerspaces continue to thrive, drawing new patrons in and engaging them as never before. This hands-on sourcebook edited by technology expert Kroski includes everything libraries need to know about the major topics, tools, and technologies relevant to makerspaces today. This collection leads librarians through how to start their own makerspace from the ground up, covering strategic planning, funding sources, starter equipment lists, space design, and safety guidelines; discusses the transformative teaching and learning opportunities that makerspaces offer, with tips on how to empower and encourage a diverse maker culture within the library; delves into 11 of the most essential technologies and tools most commonly found in makerspaces, ranging from 3D printers, Raspberry Pi, Arduino, and wearable electronics to CNC, Legos, drones, and circuitry kits; and includes an assortment of project ideas that are ready to implement. As useful for those just entering the "what if" stage as it is for those with makerspaces already up and running, this book will help libraries engage the community in their makerspaces.